THE KINETICS OF SELECTIVE HYDRAZINOLYSIS OF MALEIC ACID ON THE ACID CATALYST - S.A. Dzhumadullaeva; A.B. Bayeshov; A.V. Kolesnikov (Academic Scientific Journal of Chemistry, 2021)
For the first time, kinetics and the mechanism of the reaction of hydrazinolysis of maleic acid in the presence of cation exchanger resin KU-2-8 in H-form have been studied. The experiments were carried out in a static system in a thermostat glass reactor. It was found that cation exchanger shows high catalytic activity in the studied process - maleic acid conversion was 93%, and maleic hydrazide yield was 90%. The conversion selectivity of maleic acid to maleic hydrazide was 97,8%. The reaction rate was determined from the accumulation of maleic hydrazide. The apparent reaction rate constant (k) was calculated from the second-order reaction rate equation. The effect of initial concentrations of maleic acid and hydrazine hydrate, the temperature on the reaction rate was studied. The first order of maleic acid and hydrazine hydrate is determined. Activation energy of the process found from the Arrhenius dependence is 32,1 kJ/mol. On the basis of kinetic and IR spectroscopic methods, a probable reaction mechanism involving polymer-bound hydrogen ions is proposed